Evaluation of settlement of bored piles - Lee, Christopher Choon Sun. (2008)
The pile-soil interaction problem is very complex and is not clearly understood. Much research has been performed on the subject of determination of the ultimate pile capacity and the prediction of settlement at working load conditions. Available theoretical calculations are usually based on ideal soil conditions such as purely cohesive or cohesionless soil conditions and simplified boundary conditions, and the use of soil and pile parameters for which their precise values are uncertain. Therefore an accurate prediction of the ultimate pile capacity and the pile settlement is difficult, if not impossible.